The manager's pocket guide to mega thinking and planning / Roger Kaufman. - Kaufman, Roger A. (HRD Press, 2011)
Annotation Our world is changing and changeable. Do you know where your organization is headed? Can you justify why you should go there? And provide the criteria for judging your progress and success? This pocket guide helps you through the process of creating a better future by giving you the principles and tools of mega thinking and planning.
Keywords: Strategic planning.; Organizational change.; Organizational effectiveness.; Management.; Management; Organizational change; Organizational effectiveness; Strategic planning